Utility of dipstick test (nitrite and leukocyte esterase) and microscopic analysis of urine when compared to culture in the diagnosis of urinary tract infection in children - Fernandes, Deepthi Joella; D., Jaidev M.; Castelino, Dipthi Nishal (International Journal of Contemporary Pediatrics, 2017)
Background: Urine culture is the gold standard in the diagnosis of urinary tract infection (UTI), but usually takes at least 48 hours and is expensive. Urine dipstick test and microscopy are useful for early diagnosis and initiation of treatment. The current study aims to assess the diagnostic value of dipstick and microscopy of urine in the diagnosis of UTI in comparison with culture. Methods: Children aged between 3 months-15 years of age, in whom UTI was suspected clinically were included in the study. Dipstick and microscopic examination of urine were done and compared with the urine culture. Results were analyzed using sensitivity, specificity, positive predictive value and negative predictive values. Results: Total of 104 children with clinical suspicion of UTI were evaluated in the study. The specificity of nitrite is 93.94%, leucocyte esterase 75.76%, urine dipstick test (nitrite and leukocyte esterase) 96.97% and urine microscopy is 50% when compared to urine culture. Conclusions: Urine dipstick test (nitrite and leukocyte esterase) and urine microscopy can be used as screening tests to rule out or rule in UTI. This would be useful clinically as treatment could be commenced in children pending culture reports.